Effect of SIMASN Implementation and Employee Competence on Personnel Service Effectiveness: Evidence from the Regional Civil Service and Training Agency of Garut Regency - Nita Novianti; Mulyaningsih; Widaningsih (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This study examines the effect of SIMASN implementation and employee competence on the effectiveness of personnel services at the Regional Civil Service and Training Agency of Garut Regency. The effectiveness of personnel services is a key indicator in the digital transformation of public administration at the local government level. This study employs a quantitative approach using a survey method involving 44 respondents selected through a census technique. The variables were operationalized based on system quality, information quality, service quality, and system utilization for SIMASN implementation, as well as strategic, service execution, and interpersonal competencies for employee competence. The research instrument was tested for validity and reliability, and all items were found to be valid and reliable. The study adopted a cross-sectional design. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects. The results indicate that SIMASN implementation (B = 0.441; p < 0.05) and employee competence (B = 0.501; p < 0.05) have a positive and significant effect on service effectiveness. Simultaneously, both variables contribute 82.8% (R² = 0.828) in explaining the variation in personnel service effectiveness. These findings suggest that the effectiveness of digital-based personnel services is influenced by the combined influence of information system quality and employee competence. This study contributes to the literature by providing empirical evidence on the integration of information system implementation and human resource competence in improving public service effectiveness at the local government level.